A96: The Roller Coaster of Juvenile Idiopathic Arthritis: A Qualitative Examination of Parents' Emotional Responses to the Disease and Its Management. Issue 11 (March 2014) - Gomez‐Ramirez, Oralia; Gibbon, Michele; Berard, Roberta A.; Jurencak, Roman; Green, Jayne; Benseler, Susanne; Duffy, Ciarán M.; Tucker, Lori B.; Petty, Ross E.; Shiff, Natalie; Oen, Kiem; Brant, Rollin; et al.
Abstract : Background/Purpose: During a recent study we conducted to identify patients, parents, and clinicians' priorities in describing the course of juvenile idiopathic arthritis (JIA), parents expressed intense emotions related to the disease and its management even a decade after their children's diagnosis. Here we describe the predominant emotional experiences reported by parents and how they relate to different phases of the disease manifestation, treatments, and interactions with peers and healthcare providers. Methods: We analyzed focus group transcripts and reciprocal interview answers involving 9 experienced English‐speaking parents, 5 experienced French‐speaking parents and 8 novice parents (between 2 and 6 months since diagnosis). Their children were 2 to 16 years of age and had a variety of JIA subtypes and disease severity. Qualitative analysis included review of audio recordings to enrich transcripts (based on pauses, noises, and other non‐verbal cues), coding of emotional experiences by two investigators using a list of 69 emotion labels, coding verification by two other investigators, and analytical discussion and synthesis by our interdisciplinary team (to agree on what emotions were predominant at different stages of the disease, who or what were those emotions directed at, and how disease characteristics or parent background shaped them). Results: The time between onset and diagnosis was described by parents as a period of mounting anxiety, confusion and frustration with healthcare providers before a firm diagnosis was reached. The time shortly after diagnosis was described as a time of shock, disbelief, and fear during which parents often used denial as a coping mechanism; combined with feeling overwhelmed by a sea of information about the disease. Later in the disease course, at times of disease quiescence the predominant emotions were annoyance and worry about treatment side effects, and the fear of unpredictable flares. At times of increasing or ongoing symptoms the predominant emotions were admiration for the way their children coped with the disease, and frustration with peers and teachers that could not appreciate justification for the changes in the child's willingness to engage in physical activity and school work. This was also a time of frustration with increasing treatment and side effects. Throughout the disease parents felt a sense of powerlessness and that the disease was a "time‐consuming roller coaster." The subtype of arthritis did not affect the range of emotions experienced, but influenced the proportion of time in quiescence or ongoing symptoms, and the intensity of treatments and side‐effects. Conclusion: The emotional experiences of parents of children with JIA can be conceptualized, as a parent put it, as roller coaster ride made of intensely emotional ups and downs. This is similar to the emotional turmoil faced by parents of children with other chronic illnesses, but JIA usually does not confront them with the chronic grief produced by progressive degenerative illnesses or the threat of imminent death.